2017
DOI: 10.1111/jfpp.13453
|View full text |Cite
|
Sign up to set email alerts
|

Quality of grain and oil of maize subjected to UV‐C radiation (254 nm) for the control of weevil ( Sitophilus zeamais Motschulsky)

Abstract: The objective of this study was to evaluate the effect of UV‐C radiation in controlling the maize weevils (S. zeamais Motschulsky) in stored maize. The maize and insects (adult and immature stages) were simultaneously irradiated with UV‐C dose of 10 J/cm2. UV‐C radiation can be used as control of adult weevils because it presented a lower number of live adult weevils (33.6 counts), reduction in the loss of grain mass (15 g), and fewer damaged grains (12.9%), however, not affect the control of the immature stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In the storage at room and cooling temperatures, a decrease in the acidity index after six months of evaluation was observed, regardless of the drying temperature. The results of this study are in agreement with previous studies where in undamaged grains stored at room temperature and moisture below 12%, small variations in acidity levels occurred 26 , 62 .…”
Section: Resultssupporting
confidence: 93%
“…In the storage at room and cooling temperatures, a decrease in the acidity index after six months of evaluation was observed, regardless of the drying temperature. The results of this study are in agreement with previous studies where in undamaged grains stored at room temperature and moisture below 12%, small variations in acidity levels occurred 26 , 62 .…”
Section: Resultssupporting
confidence: 93%
“…Hamid and Jawaid (2011) reported that pretreatments with UV-A and UV-C radiations stimulated the germination and growth of Mung bean through auxin biosynthesis. It has already been known that UV-C radiation improves the seed quality and germination in crop seeds prior to sowing, owing to its antifungal capacity (Ferreira et al 2018). On the other hand, our results were in line with the study of Rahimzadeh et al (2011) who revealed that the growth inhibition effect of UV-C was much more severe than that of UV-A in Satureja hortensis seedlings.…”
Section: Resultsmentioning
confidence: 99%